Integrating Job Safety Analysis and Risk Assessment for Occupational Safety in Task-Based Sulfur Mining Activities - Rinawiyanti, Esti Dwi; Kusumo, Argo Hadi; Sari Dewi, Dian Retno; Irawan, Fellychita Cindy (Universitas Katolik Parahyangan, 2026)
Purpose: This study aims to identify occupational hazards, assess risk levels, and propose appropriate risk control measures in task-based sulfur mining activities, which are characterised by high-risk environmental and manual work conditions. Methodology: A mixed qualitative–quantitative approach was employed. Data were collected through direct observation and semi-structured interviews involving five sulfur miners and one company representative at a sulfur mining site in Banyuwangi, Indonesia. Job Safety Analysis (JSA) was used to systematically identify hazards in each work step, while risk levels were evaluated using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method based on likelihood and severity scales adapted from AS/NZS 4360. Risk scoring was validated through iterative discussions with the participants. Results: A total of 25 potential hazards were identified across key activities, including climbing, sulfur extraction, and material handling. Of these, 21 hazards were classified as medium risk and 4 as low risk. The main hazards include uneven terrain, steep pathways, toxic gas exposure, and manual material handling. Proposed control measures include engineering improvements (e.g., path levelling and guardrails), administrative controls (e.g., training and work procedures), and the use of personal protective equipment. Conclusion: The integration of JSA and HIRARC effectively provides a structured approach for identifying and assessing risks in dynamic mining environments. Originality: This study contributes by applying JSA–HIRARC integration in a non-controlled outdoor mining context, highlighting environmental and ergonomic risk factors that are often overlooked in previous studies.